1996
DOI: 10.1073/pnas.93.16.8739
|View full text |Cite
|
Sign up to set email alerts
|

16 alpha-substituted analogs of the antiprogestin RU486 induce a unique conformation in the human progesterone receptor resulting in mixed agonist activity.

Abstract: Previously, we have shown that agonists and antagonists interact with distinct, though overlapping regions within the human progesterone receptor (hPR) resulting in the formation of structurally different complexes. Thus, a link was established between the structure of a ligand-receptor complex and biological activity. In this study, we have utilized a series of in vitro assays with which to study hPR pharmacology and have identified a third class of hPR ligands that induce a receptor conformation which is dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
32
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 27 publications
4
32
0
1
Order By: Relevance
“…Numerous studies on estrogen and progesterone receptors have indicated that a range of distinct receptor conformations can be induced by the binding of different ligands. There is a strong correlation between receptor conformations elicited by different ligands and downstream biological activity (9)(10)(11)(12)(13). The hypothesis that different PPA Rligands have distinct downstream effects is supported by our protein profiling experiment that demonstrated differential regulation of gene expression by troglitazone and rosiglitazone in several cell types.…”
Section: A B Csupporting
confidence: 60%
See 1 more Smart Citation
“…Numerous studies on estrogen and progesterone receptors have indicated that a range of distinct receptor conformations can be induced by the binding of different ligands. There is a strong correlation between receptor conformations elicited by different ligands and downstream biological activity (9)(10)(11)(12)(13). The hypothesis that different PPA Rligands have distinct downstream effects is supported by our protein profiling experiment that demonstrated differential regulation of gene expression by troglitazone and rosiglitazone in several cell types.…”
Section: A B Csupporting
confidence: 60%
“…It has been postulated that these coactivators act as bridges to transmit the nuclear receptor regulatory signals to the cellular transcriptional machinery. Studies on estrogen and progesterone receptors have suggested that a range of distinct receptor conformations can be induced by the binding of different ligands (9)(10)(11)(12)(13). Although less is known about PPA R-in this regard, it is possible that different PPA R-ligands induce unique conformational changes in the receptor, eliciting distinct downstream biological effects.…”
mentioning
confidence: 99%
“…In another study, Fjelldal et al (37) exposed breast cancer and uterine cervix cancer cells to P4 or RU486 and found that, depending on the dose of both agents, the treatments could reduce cell density in vitro and were not due to their actions on the intranuclear P4 receptor. However, there are some data showing that RU486 may not be as highly specific as a P4 antagonist because of its partial PR-agonist activity (41,42). Here, we can also speculate that one of the reasons for its complex and sometimes contradictory effects is that RU486 is a selective blocker of PR-B only and does not block PR-A.…”
Section: Discussionmentioning
confidence: 92%
“…As with estrogen receptor (ER) mixed agonists, the relative agonist, or antagonist, activity of PR mixed agonists is influenced by the cell and promoter context (7,38). The likely mechanistic basis for the unique activities of the PR mixed agonists was revealed when it was shown by limited protease digestion analysis that these ligands induce a conformational change within PR which is different from that induced by either agonists or antagonists (41). These studies firmly established a link between the overall structure of the PR-ligand complex and its biological activity.…”
mentioning
confidence: 99%
“…In addition to agonists and antagonists, we have recently identified a new class of PR ligands which function as mixed agonists (41). As with estrogen receptor (ER) mixed agonists, the relative agonist, or antagonist, activity of PR mixed agonists is influenced by the cell and promoter context (7,38).…”
mentioning
confidence: 99%